A quantified epistemic logic for reasoning about multi-agent systems - Belardinelli,F; Lomuscio,A (2007)
We investigate quantified interpreted systems, a semantics for multiagent systems in which agents can reason about individuals, their properties, and the relationships among them. We analyse a first-order epistemic language interpreted on this semantics and show soundness and completeness of Q.S5n, an axiomatisation for these structures. © 2007 IFAAMAS.